Pengaruh Sarana Prasarana Laboratorium dan Motivasi Kerja Guru Terhadap Etos Kerja Guru - Rusmala Dewi; Yasir Araffat; Nurlina Nurlina (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The purpose of this study was to determine the influence of laboratory infrastructure and teacher work motivation on the work ethic of teachers at SMP Negeri Se, Prabumulih Timur District. This research was conducted at State Junior High Schools throughout East Prabumulih District. Researchers chose (SMP Negeri 5 Prabumulih, SMP Negeri 8 Prabumulih and SMP Negeri 12 Prabumulih). This research belongs to the type of expost facto research. The population in this study was 162 people with the number of samples in this study amounting to 114 people. Data collection techniques use observation, questionnaires and documentation. Data analysis techniques use normality tests, linearity tests, multicholinearity tests, simple correlation analysis, double correlation analysis, simple regression analysis, t test and F test. The results of this study are: there is a significant influence of laboratory facilities and infrastructure on the work ethic of teachers of SMP Negeri Se Kecamatan Prabumulih Timur; there is a significant influence of teacher work motivation on the work ethic of teachers at SMP Negeri Se Kecamatan Prabumulih Timur; there is a significant influence of laboratory facilities and infrastructure and teacher work motivation together on the work ethic of teachers of SMP Negeri Se, Prabumulih Timur District. In conclusion, there is an influence of laboratory infrastructure and teacher work motivation on teacher work ethic Keywords: Facilities and Infrastructure; Laboratory; Work motivation; Work Ethic